The protective role of oily fish intake against type 2 diabetes: insights from a genetic correlation and Mendelian randomization study - Zhang, Youqian; Ren, Entong; Zhang, Chunlong; Wang, Yang; Chen, Xiaohe; Li, Lin (Frontiers in Nutrition, 2024)
All authors contributed to the study's conception and design. Material preparation, data collection, and analysis were performed by Xiaohe Chen, Yang Wang, and Youqian Zhang. Paper retouching by Lin Li. Format modification by Chunlong Zhang and Entong Ren. The first draft of the manuscript was written by Youqian Zhang and all authors commented on previous versions of the manuscript. All authors read and approved the final manuscript.Each investigation incorporated within the GWAS framework was sanctioned by the relevant ethical review panels Please see the original article citing the GWAS article for the specific approval documents ethics approval was necessary for this research.